Pelatihan Praktikum Kreatifitas dengan Membuat Alat Sentrifugasi Sederhana di Sekolah Lentera Harapan Gunung Moria - Pingkan Imelda Wuisan; Grace Niche Agnesa Silaban; Laura Filadelfi; Dwi Pareanza Maharaja; Andreas Rambe; Wahyu Irawati (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2026)
The situational analysis revealed that students of Sekolah Lentera Harapan Gunung Moria, originating from the interior regions of Papua, generally have limited experience in using scientific laboratory equipment due to inadequate facilities and restricted access to laboratories. This gap has contributed to their low level of conceptual understanding in science learning. This Community Service Program (PkM) aimed to conduct a training workshop on constructing a simple centrifugation device designed from easily accessible materials without relying on standard laboratory equipment. The implementation methods included: (1) preparation of the centrifugation device prototype, (2) training sessions and intensive mentoring conducted by lecturers and students from the Biology Education Study Program, and (3) evaluation through interviews. The activity was integrated with the Laboratory Management course using a Project-Based Learning approach. The program was held on Thursday, April 24, 2024, at SLH Gunung Moria, Jalan Boulevard M.H. Thamrin No. 1100, Kelapa Dua, Tangerang, Banten, involving 20 students. The evaluation results indicated that the activity improved students’ understanding of centrifugation principles as well as their skills in assembling and operating the device independently. This small fan-based innovation provided contextual and practical learning experiences while fostering students’ creativity in conducting science practicum activities without laboratory facilities.